Gambaran Usia, Jenis Kelamin, Kebiasaan Olah Raga, dan Kelelahan Kerja Pengerajin Tenun di Yogyakarta - Yustinus Denny Ardyanto Wahyudino; Nur Afni Sharfina; Ismaul Ma’arif (Syntax Literate, 2023)
Work fatigue is a problem that continues to elude the attention of industrial workers, especially weavers. Worker productivity can suffer as a result of prolonged weariness. Multiple reasons, both internally and externally, are suspected of contributing to work fatigue. The aim of the research is to identify the extent to which internal factors such as age, gender, and exercise routines of weavers with work fatigue are influenced. The design of the research is cross-sectional, which means data is accumulated only once. This research had 87 respondents as a research sample selected using the total sampling technique. The results of the research revealed that the average age of the respondents (47.1%) was between 56 -65 years old, mayority the weavers was female (67.8%). The research additionally identified a correlation between gender, age, and exercise routines and work fatigue among weavers in Special Region of Yogyakarta